Development of Gamification Linear Algebra Application Using Storytelling - Rahim R.H.A.; Tanalol S.H.; Ismail R.; Baharum A.; Rahim E.A.; Noor N.A.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electroencephalography; Students; Teaching; Application development process; Electro-encephalogram (EEG); Gamification; Lack of confidences; storytelling; Student engagement; Teaching and learning; Tool applications; Linear algebra